KINETICS OF OXIDATION OF UNSATURATED ACID BY THALLIUM(III) IN AQUEOUS ACETIC ACID AND MICELLAR MEDIUM - Jilane, Jafar; Sharma, K.N. (International Journal of Research -GRANTHAALAYAH, 2025)
The oxidation of α-crotonic acid by thallium (III) perchlorate proceeds by a mechanism approach involving direct two-electron transfer with lack of free radical intervention from substrate to the oxidant via an intermediate complex. The stoichiometry (1:1) of the reaction followed by its decomposition in a rate-determining step to product acetaldehyde. The orders in oxidant and acid were found to be unity, whereas solvent, micellar (CTAB) exhibited fraction-order kinetics. The activation parameters were also discussed.